Pendidikan Antikorupsi Kepada Siswa Sekolah Dasar Dengan Metode Storytelling - Naurissa Biasini; Clara Moningka; Emma R Aliudin; Suci Marini (Universitas Katolik Soegijapranata, 2020)
The level of corruption in Indonesia has not decreased significantly even though there have been severe criminal penalties and prevention systems carried out. It is considered that the behavior of corruption is taken root in the mentality of the Indonesian people. Therefore, anti-corruption education needs to be provided early to reduce the possibility of someone to commit corruption when they are adults. The right education method can provide significant results in achieving educational goals to be achieved. The Community Service Team of the Communication Science and Psychology Study Program at Universitas Pembangunan Jaya held an anti-corruption education for elementary school students in collaboration with Sawah Baru Elementary School. The target of this program is elementary school students in grades 3, 4 and 5. In this anti-corruption education, the team used storytelling methods to facilitate and increase understanding in participant's mind. It turns out that this storytelling method has a large impact on the understanding of corruption in the view of elementary school students. In the future, we hope anticorruption education can be held in every school or into the education curriculum.